Peroxisomal Proteome Mining of Sweet Pepper (Capsicum annuum L.) Fruit Ripening Through Whole Isobaric Tags for Relative and Absolute Quantitation Analysis - González-Gordo, Salvador; Palma, José M.; Corpas, Francisco J. (Frontiers in Plant Science, 2022)
Peroxisomes are ubiquitous organelles in eukaryotic cells characterized by an active nitro-oxidative metabolism which have a relevant metabolic plasticity depending on the organism, tissue, developmental stage, or physiological/stress/environmental conditions. The knowledge of peroxisome from fruits is very limited and much less about its proteome. Using sweet pepper (Capsicum annuum L.) fruits at two ripening stages (immature green and ripe red), it was analyzed the proteomic peroxisomal composition by quantitative isobaric tags for relative and absolute quantitation (iTRAQ)-based protein profiling. For this aim, it was accomplished a comparative analysis of the pepper fruit proteome obtained by iTRAQ versus the identified Arabidopsis thaliana peroxisomal protein profile. This allowed identifying 56 peroxisomal proteins. Among these proteins, 48 were located in the peroxisomal matrix, 35 proteins had a peroxisomal targeting signal type 1 (PTS1), 8 had a PTS type 2, 5 lacked this type of peptide signal, and 8 proteins were associated with the membrane of this organelle. Furthermore, 34 proteins showed significant differences during the ripening of the fruits, 19 being overexpressed and 15 repressed) process. Some of the identified peroxisomal proteins could be expected as part of the pepper fruit antioxidant metabolism (catalase, superoxide dismutase, ascorbate peroxidase), the β-oxidation (acyl-coenzyme A oxidase, 3-hydroxyacyl-CoA dehydrogenase, enoyl-CoA hydratase), although other identified proteins could be considered “new” or “unexpected” in fruit peroxisomes like urate oxidase (UO), sulfite oxidase (SO), 5-methyltetrahydropteroyltriglutamate-homocysteine methyltransferase (METE1), 12-oxophytodienoate reductase 3 (OPR3) or 4-coumarate-CoA ligase (4CL), which participate in different metabolic pathways such as purine, sulfur, L-methionine, jasmonic acid (JA) or phenylpropanoid metabolisms. In summary, the present data provide new insights into the complex metabolic machinery of peroxisomes in fruit and open new windows of research in the peroxisomal functions during fruit ripening.